The Growth of Leptolyngbya HS-16 and HS-36 on 35oC with pH Variation (Indonesian Society for microbiology, 2018)
The observation of Leptolyngbya growth on temperature 35oC with initial pH variation had been done. The study was descriptive research. The study aimed to determine the best initial growth pH for Leptolyngbya HS (Hot Spring)-16 and HS-36. Leptolyngbya HS-16 was isolated from Pancar Mountain hotspring, while Leptolyngbya HS-36 was isolated from Maribaya hot spring. Â The acidity (pH) of Pancar mountain and Maribaya hot spring was 7. Each strain was grown in Blue Green medium number 11 (BG-11) with variation initial pH (6, 7, 8 and 9) and incubated on 35 oC. Parameters was wet biomass weight of Leptolyngbya in each strain. Observation were made on 15 days with 11 sampling. From the observation, the average of wet biomass weight of Leptolyngbya HS-16 was obtained at pH 6 (0,0295 g/L), pH 7 (0,0404 g/L), pH 8 (0,03825 g/L), and pH 9 (0,02735 g/L), meanwhile Leptolyngbya HS-36 was obtained at pH 6 (0,02905 g/L), pH 7 (0,01995 g/L), pH 8 (0,05345 g/L) and pH 9 (0,05995 g/L) on the 15th day. The results of 15 days observation showed that the best initial pH for growing Leptolyngbya HS-16 is 7, while Leptolyngbya HS-36 is 9. From this study it could be seen that Leptolyngbya HS-16 and HS-36 could be cultured with alkaline condition.Â